AFAP1L1, a novel associating partner with vinculin, modulates cellular morphology and motility, and promotes the progression of colorectal cancers. (10th April 2014) - Takahashi, Ryo; Nagayama, Satoshi; Furu, Moritoshi; Kajita, Yoichiro; Jin, YongHui; Kato, Tomohisa; Imoto, Seiya; Sakai, Yoshiharu; Toguchida, Junya
Abstract We have previously identified actin filament‐associated protein 1‐like 1 (AFAP1L1) as a metastasis‐predicting marker for spindle cell sarcomas by gene expression profiling, and demonstrated that AFAP1L1 is involved in the cell invasion process by in vitro analyses. However, its precise molecular function has not been fully elucidated, and it remains unknown whether AFAP1L1 could be a prognostic marker and/or therapeutic target of other malignancies. In this study, we found a marked elevation of AFAP1L1 gene expression in colorectal cancer (CRC) tissues as compared to the adjacent normal mucosa. Multivariate analysis revealed that AFAP1L1 was an independent and significant factor for the recurrence of rectal cancers. Moreover, the addition of the AFAP1L1 expression level to the lymph node metastasis status provided more predictive information regarding postoperative recurrence in rectal cancers. AFAP1L1‐transduced CRC cells exhibited a rounded shape, increased cell motility on planar substrates, and resistance to anoikis in vitro. AFAP1L1 localized to the ringed structure of the invadopodia, together with vinculin, and AFAP1L1 was identified as a novel associating partner of vinculin by immunoprecipitation assay. AFAP1L1‐transduced cells showed accelerated tumor growth in vivo, presumably reflecting the anoikis resistance of these AFAP1L1‐expressing cells. Furthermore, the local administration of a siRNA against AFAP1L1 significantly suppressed the in vivo tumor growth of xenografts, suggesting that AFAP1L1 might be a candidate therapeutic target for CRCs. These results suggest that AFAP1L1 plays a role in the progression of CRCs by modulating cell shape and motility and by inhibiting anoikis, presumably through interactions with vinculin‐including protein complexes.